The Effects of Trust and Service Quality on Customer Loyalty of Islamic Banks Moderated By Religiosity (A Study of Islamic Bank Customers in Jakarta) - Irma Rasita Gloria Barus; Hery Winoto Tj; Soegeng Wahyoedi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The objective of this study was to analyze the impact of trust and service quality on customer loyalty of Islamic Banks in which religiosity plays a role as moderator. This study identified how trust and service quality of Islamic banks in terms of their conformity with Sharia principles and their safe handling of deposits affect costumer loyalty towards them. The data for the study were collected through questionnaires from 120 individuals participated in the survey using accidental sampling method. The data were analyzed through structural equation modelling – partial least square (SEM-PLS) with WarpPLS 7.0 version of software. The results showed that trust had a positive impact on loyalty of Islamic banks customers. Moreover, it was confirmed that service quality had a positive relationship with customer loyalty of Islamic banks. However, the results could not identify any significant moderating role of religiosity on the relationship between trust on loyalty and service quality on loyalty.